The Role of Parenting Styles in Shaping Adolescents’ Altruistic Attitudes - Nady Ramanda; Syawaluddin Nasution (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2025)
This study aims to determine the role of parenting styles on adolescent altruism. Altruism, defined as helping others without expecting anything in return, is an important aspect of adolescent social and moral development. This study involved three parents and three adolescents aged 16-17 years in Pahlawan Village, Medan Perjuangan District. The research method used was descriptive qualitative. Data were collected through interviews that measured parenting styles (authoritarian, democratic, and permissive) and levels of adolescent altruism. The results showed that democratic parenting had a significant and positive relationship with adolescents' altruistic attitudes. Adolescents raised in three democratic parenting styles tended to have higher altruistic attitudes. Conversely, authoritarian and permissive parenting did not show a statistically significant relationship with altruistic attitudes. This study concludes that parenting styles that emphasize discussion, emotional warmth, and the giving of responsibility (democratic) play an important role in shaping caring and helpful personalities. These findings have practical implications for parents and educators to focus more on approaches that promote empathy and cooperation in educating children